A Practical Cardiovascular Health Assessment for Manual Wheelchair Users During the 6-Minute Push Test - Maja Goršič; Madisyn R. Adelman; Grace McClatchey; Jacob R. Rammer (Sensors)
Traditional VO2max testing methods are often impractical for manual wheelchair users, as they rely on lower-body exercise protocols, require specialized equipment, and trained personnel. The 6-Minute Push Test (6MPT) is a widely used cardiovascular assessment that may provide a feasible alternative for estimating aerobic capacity in this population. This study aimed to develop a predictive model for VO2max using physiological variables recorded during the 6MPT. Twenty-eight participants (14 novice and 14 expert manual wheelchair users) completed the test while wearing a VO2 mask and heart rate monitor. Spearman correlation analysis showed that distance covered during the 6MPT significantly correlated with VO2max (r = 0.685, p < 0.001). A stepwise linear regression identified two predictive models: one using distance alone (R2 = 0.416, p < 0.001) and another incorporating both distance and maximum heart rate (R2 = 0.561, p < 0.001). These models offer practical estimations of VO2max, eliminating separate protocols. Our findings suggest that the 6MPT can serve as a simple, cost-effective alternative to laboratory-based VO2 testing, facilitating routine cardiovascular fitness assessments for manual wheelchair users in clinical and community settings. Future research should focus on validating these models in a larger, more diverse cohort to enhance their generalizability.